Paeoniflorin reduces the spinal cord injury in rats through TLR4 inflammatory pathway and Nrf2 oxidative stress pathway: the experimental study - Li-Cai Zhang (Journal of Hainan Medical University, 2017)
Objective: To study the effect of paeoniflorin on TLR4 inflammatory pathway and Nrf2 oxidative stress pathway in rat model with spinal cord injury. Methods: Male SD rats were selected and divided into sham group, spinal cord injury group and paeoniflorin group, spinal cord injury rat models were established and then given 30 mg/kg paeoniflorin for 14 d of intervention in a row, and then serum and spinal cord specimens were collected to determine the expression of cell apoptosis genes, TLR4 pathway genes and Nrf-2 pathway genes. Results: Spinal cord caspase-3, caspase-8, caspase-9, TLR4, MyD88, NF-kB, AP-1, Nrf-2 and ARE mRNA expression as well as serum IL-6, TNF-α and IL-12 contents of spinal cord injury group were significantly higher than those of sham group while spinal cord HO-1, SOD and GSH-PX contents were significantly lower than those of sham group; spinal cord caspase-3, caspase-8, caspase-9, TLR4, MyD88, NF-kB and AP-1 mRNA expression as well as serum IL-6, TNF-α and IL-12 contents of paeoniflorin group were significantly lower than those of spinal cord injury group while spinal cord Nrf-2 and ARE mRNA expression as well as HO-1, SOD and GSH-PX contents were significantly higher than those of spinal cord injury group. Conclusion: Paeoniflorin can inhibit the TLR4 inflammatory pathway and enhance the Nrf2 anti-oxidative stress pathway to reduce the spinal cord injury and inhibit cell apoptosis in rats.